Comparison of neo-pharmatherapy and volume building therapy in USSL - Suratwala, Narendra B.; Suratwala, Jay N.; Jadawala, H. D. (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Objective of the study was to identify healthy individuals with idiopathic unilateral sudden hearing loss (USSL) and treating them under either of two different therapeutic protocols to judge the hearing recovery. Methods: Prospective crossover series study of 72 adult patients (males and females) of Indian origin was performed. Diagnosis of USSL and treating under two different protocols as; Group "A" was treated with oral combination form of Vinpocetine, Q-enzyme, Piracetam and B. Serrata over 3 months; while Group "B" was treated with Plasma expander IV Dextran, IV Dexamethasone, I/M Cyanocobalamine and Cyclandelate for 5 days followed by oral Dexametasone for 5 days Methycobalamine over 3 months. Common audiological and communicative parameters were applied in both treated groups to assess and analyse the responses incurred at the end of treatment. The graded system was applied to evaluate the SRT. Better outcomes based on the trialed drugs and their action is assessed. Results: 61 of 72 patients successfully completed the regimes. After applying Siegel’s grading for judging the SRT gains; group A had 16, 10 and 5 with grade I, II, III recovery while group B had 8, 6, 16 with grades I, II, III recovery respectively. It was noticed that group A patients showed earlier recovery of higher frequencies. Conclusions: Both subject groups showed improved BC gains at end treatment. There was marked hearing recovery (Gr. I, II-Siegel’s classification) in group "A" was (78%) which is significant over group "B" (50%) and above natural recovery rate.